A ruthenium–oligonucleotide bioconjugated photosensitizing aptamer for cancer cell specific photodynamic therapy. Issue 1 (9th November 2021) - McKenzie, Luke K.; Flamme, Marie; Felder, Patrick S.; Karges, Johannes; Bonhomme, Frederic; Gandioso, Albert; Malosse, Christian; Gasser, Gilles; Hollenstein, Marcel
Abstract : Ruthenium complexes have emerged as a promising class of compounds for use as photosensitizers in photodynamic therapy. Direct conjugation to aptamers enhances their therapeutic usefulness by conveying specificity to Ru-mediated PDT. Abstract : Ruthenium complexes have emerged as a promising class of compounds for use as photosensitizers (PSs) in photodynamic therapy (PDT) due to their attractive photophysical properties and relative ease of chemical alteration. While promising, they generally are not inherently targeting to disease sites and may therefore be prone to side effects and require higher doses. Aptamers are short oligonucleotides that bind specific targets with high affinity. One such aptamer is AS1411, a nucleolin targeting, G-quadruplex forming, DNA aptamer. Here we present the first example of direct conjugation of a Ru(ii ) polypyridyl complex-based PS to an aptamer and an assessment of its in vitro cancer cell specific photosensitization including discussion of the challenges faced.